Meningkatkan Kemampuan Menulis Siswa Kelas VII pada Cerita Fabel Melalui Media Gambar Berseri di SMP Negeri 3 Simpang Kiri - Erna Afrianty Tinendung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Improving fable writing for class VII students through various visual media at Simpangkiri State Middle School. Researchers used descriptive methods with Classroom Action Procedures (PTK). The survey also revealed that there were 17 grade 7 students at SMP N 3 Simpang Kiri and there were several interesting stories created by the students. The cycle results also showed that there were 17 grade 7 students at SMP N 3 Simpang Kiri whose students created several interesting fairy tales. Nine students came up with very interesting tales. Based on the assessment of the ability to write fables using visual media in Cycle II, the results showed that 12 out of 17 students wrote very interesting fables. This is proven by the assessment of teachers and researchers that these 12 students wrote fairy tales using various visual media which were very interesting and imaginative.